Correlations Between ASSR Based on Narrow-Band CE® Chirp, Click ABR, and Tone-Burst ABR in Audiological Evaluation of Children Under Anesthesia - Karolina P. Sideri; Laura F. Chiriboga; Piotr Henryk Skarzynski; Magdalena Beata Skarzynska; Milaine D. Sanfins; Maria F. Colella-Santos (Life)
Hearing plays a significant role in children’s development. The Auditory Steady State Response (ASSR) using a narrow band CE® chirp is a technique that allows multiple stimuli to be presented simultaneously, making it possible to obtain electrophysiological thresholds with frequency specificity. The objective of this work is to analyze the findings obtained with the ASSR NB-CE® chirp technique and compare them with two other methodologies—click ABR and tone-burst ABR—in the audiological assessment of children carried out under inhalation anesthesia. All the exams were performed in a single session. This study involved 71 children aged between 14 and 59 months, male and female, who were referred for ABR and ASSR due to suspected hearing loss and/or delay in speech/language development. Pearson’s correlation coefficient between the uncorrected and corrected thresholds obtained in the three methods demonstrated high correlations for all frequencies evaluated.